International arms trade: Revealed political preferences or cartel behaviour? - Hans H. Glismann; Ernst-Jürgen Horn (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1988)
On the basis of a world matrix of international trade in majorconventional weapons for 1985, a comparison is made between the regional structure of arms trade and the regional structure of trade in civilian goods from a comparable technological background. It turns out that there are striking divergencies between both kinds of trade structures, even within military alliances. These divergencies are then captured by an indicator which is named revealed political preference (RPP). It is argued that introducing a free-trade regime within NATO and other industrialised western countries would make arms trade increase, and, in particular, make the shares of Japan and West Germany in arms exports rise manifold, thereby raising world economic welfare. It is suggested that different hypotheses for explaining world arms-trade structures are relevant according to the region analysed, like the trading-with-the-enemy hypothesis with respect to the arms trade between advanced and less-developed countries, or the military-industrial-complex hypothesis for arms trade within alliances.
Keywords: 330; Rüstungsgut